A Review: Schiff Bases as Promising Agents and Their Pharmaceutical Applications - Kamil, Ahmed; Jassim Hamzah, Mohammed (Journal of Pharmacology and Drug Development, 2026)
Schiff bases have been a very important category of chemical molecules in medicine and pharmacology over the last several decades. Their structure contains an azomethine functional group (-C=N-).This group is typically formed by the condensation of primary amines with aldehydes or ketones. Schiff bases are relatively easy to synthesize, and their structural versatility allows modification for diverse biological applications. From a medicinal standpoint, Schiff bases have demonstrated a wide range of biological activities, including antimicrobial, anticancer, anti-inflammatory, antioxidant, and antiviral effects.Multiple studies suggest that even small alterations in chemical structure, such changes in substituent characteristics or the introduction of heterocyclic groups, may substantially affect biological efficacy. Schiff bases are also recognized for their ability to coordinate with metal ions, which has led to the development of numerous metal complexes with new or improved pharmacological characteristics.The medicinal significance of Schiff bases is further supported by their proposed mechanisms of action, including enzyme inhibition, interaction with microbial cell membranes, DNA binding, and modulation of oxidative stress pathways.These characteristics make Schiff bases attractive frameworks for the development of novel therapeutic agents.This review aims to highlight the pharmaceutical importance of Schiff bases by focusing on their chemical characteristics and key antibacterial, antifungal, antiviral, and anticancer activities, while also discussing their potential applications in drug discovery and development.